The implementation of TikTok live shopping: an Islamic business ethics perspective - Khairul Anwar; Nurul Wahidah; Dina Nur Amilah Balbisi (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2024)
The rapid advancement of digital technology has transformed business practices, with social media platforms like TikTok emerging as influential marketing channels, particularly through live-streaming shopping features. Despite its high conversion rates and global growth, this trend raises ethical concerns, especially in Muslim-majority contexts like Indonesia, where consumer trust hinges on sharia-compliant practices. This study examines the application of Islamic business ethics –justice, honesty, free will, mutual benefit, and moral integrity– in TikTok live shopping, addressing gaps between its economic potential and ethical challenges. Using a qualitative library research methodology, the study analyzes secondary sources, including academic literature and empirical findings, to evaluate TikTok’s live-streaming practices through an Islamic ethical lens. Results indicate that integrating sharia principles, such as transparency and accountability, enhances consumer trust and transactional fairness, though challenges like misleading promotions and prohibited products persist. The study contributes to the discourse on ethical digital commerce by proposing a framework for aligning live-streaming commerce with Islamic values, emphasizing the need for regulatory oversight and platform-level compliance mechanisms.